The Efficacy of Alendronate Versus Denosumab on Major Osteoporotic Fracture Risk in Elderly Patients With Diabetes Mellitus: A Danish Retrospective Cohort Study - Viggers, Rikke; Al-Mashhadi, Zheer; Starup-Linde, Jakob; Vestergaard, Peter (Frontiers in Endocrinology, 2022)
Objective: Patients with diabetes mellitus have an increased risk of fractures, however, the underlying mechanism is largely unknown. We aimed to investigate whether the risk of major osteoporotic fractures in diabetes patients differs between subjects initiated with alendronate and denosumab, respectively. Methods and research design: We conducted a retrospective nationwide cohort study through access to all discharge diagnoses (ICD-10 system) from the National Danish Patient Registry along with all redeemed drug prescriptions (ATC classification system) from the Health Service Prescription Registry. We identified all subjects with a diabetes diagnosis between 2000 and 2018 and collected data on first new prescription of anti-osteoporotic treatment between 2011-2018. Exposure was defined as either alendronate or denosumab treatment initiated after diabetes diagnosis. Outcome information was collected by identification of all major osteoporotic fracture (MOF) diagnoses, i.e., hip, spine, forearm and humerus, from exposure until 2018 or censoring by emigration or death. The risk of fracture was calculated as hazard ratios (HR) using multiply adjusted cox proportional models with death as a competing risk. Results: We included 8,745 subjects initiated with either alendronate (n=8,255) or denosumab (n=490). The cohort consisted of subjects with a mean age of 73.62 (SD ±9.27) years, primarily females (69%) and suffering mainly from type 2 diabetes (98.22%) with a median diabetes duration at baseline of 5.45 years (IQR 2.41-9.19). Those in the denosumab group were older (mean 75.60 [SD ±9.72] versus 73.51 [SD ±9.23] years), had a higher proportion of women (81% versus 68%, RR 1.18 [95% CI 1.13-1.24] and were more comorbid (mean CCI 2.68 [95% CI 2.47-2.88] versus 1.98 [95% CI 1.93-2.02]) compared to alendronate initiators. In addition, denosumab users had a higher prevalence of previous fractures (64% versus 46%, RR 1.38 [95% CI 1.28-1.48]). The adjusted HR for any MOF after treatment initiation with denosumab was 0.89 (95% CI 0.78-1.02) compared to initiation with alendronate. Conclusion: The risk of incident MOF among subjects with diabetes was similar between those initially treated with alendronate and denosumab. These findings indicate that the two treatment strategies are equally effective in preventing osteoporotic fractures in subjects with diabetes.